ANALISIS KELELAHAN KERJA OPERATOR PRODUKSI MENGGUNAKAN METODE CARDIOVASCULAR LOAD (CVL) DAN INDUSTRIAL FATIQUE RESEARCH COMMITTEE (IFRC) (Studi kasus PT. Alis Jaya Cipta Tama) - Arby Yudha Maulana; Ferida Yuamita (Jurnal Cakrawala Ilmiah, 2023)
Naturally, there are risks associated with every job, including work-related stress, burnout, and accidents. In both formal and informal work settings, fatigue is a problem that needs specific care. Workers who are fatigued at work may perform less well and make more mistakes. The Cardiovascular load (CVL) method is a method for determining the level of work fatigue in terms of the operator's pulse, while the IFRC (Industrial Fatigue Research Committee) method measures fatigue level subjectively by distributing questionnaires. This study aims to identify work fatigue and analyze the relationship between age, length of service, nutritional status, work attitude and workload with work fatigue at mill section 1 operator PT Alis Jaya Ciptatama located in Klaten, Central Java. The calculation results show that the %CVL ranges from 11.6% to 34.1%, placing it in the mild category and indicating no fatigue. The results of IFRC calculations show that operators experience work fatigue of 88% and high fatigue of 12%. Results of the study: Respondents who were at risk of work burnout (≥35 years) were (16%), tenure at work were at risk of work burnout (≥ 8 years) by (44%), under and over nutrition status by (52%), work attitude at risk (72%) and workload at risk (44%). Conclusion: There is no effect of work fatigue on work fatigue in terms of CVL calculations after testing the data through multiple linear regression. There is a relationship between work fatigue (sig age = 0.029 and length of service = 0.013) and work fatigue in terms of IFRC calculations after testing the data through multiple linear regression.